THU0205 RESPONSE TO SMALL MOLECULES IS MOSTLY DRIVEN BY PATIENT GLOBAL ASSESSMENT OF DISEASE: A REAL WORLD OBSERVATION. (2nd June 2020) - Joseph, C.; Bilgrami, S. M.; Ottewell, L.; Gray, L.; Mitchell, W.; Wood, F.; Massarotti, M.; Bukhari, M.
Abstract : Background: Two Small molecules (Tofacitinib and Baricitinib) have been licensed in the UK for the use in rheumatoid arthritis. Their licensing came from several studies that showed good efficacy with baricitinib (1) study showing superior efficacy to adalimumab and tofacitinib showing non inferiority to TNF drugs (2). The response has also been shown in patient reported outcomes (find reference). Response when measure using the DAS score has two relatively subjective components (tender joints and patient global assessment) and two relatively objective components (Swollen joints and inflammatory markers) Objectives: To determine in a real world setting if the response to small molecules is mostly due to a drop in subjective or objective components of the DAS score Methods: A retrospective chart review was done on all new starters on small molecules in a district hospital in the North of England. Data were collected at baseline, three months and six months from October 2018 to date. Drop in the components of the DAS28 score was calculated and overall drop in DAS28 was modelled as the explanatory variable using linear regression modelling. This was the done Adjusting for age gender and duration of disease. Sensitivity of the model was examined using a logistic model of EULAR moderate/good response and using adjusted R squared estimates for linear model of improvement of the DAS28 score. Results: 76 patients were included in the analysis from 85 starters on small molecules.61 (71.8 %) were on baricitinib and the baseline median DAS28 score was .5.97 (IQR 5.35, 6.55)The median drop at three months in the DAS28 score was 2.42 (IQR 1.33, 3.31). and at six months was 2.77 (IQR 2.01, 3.83). There was numerical relative increased efficacy of baricitinib but this was not statistically significant (DAS drop at three months 2.54 IQR 1.73, 3.09 vs 2.12 IQR 1.51, 3.5). The relative contribution of the individual components of the DAS score to the drop ae in DAS are shown in table 1 below. Sensitivity analysis looking at predictors of a DAS drop of >0.6 confirmed this finding. Conclusion: In this real world observational study, there was a good response to both small molecules with numerical better response to baricitinib. Tender joint count and patient global response accounted for more of the drop in DAS28 than swollen joints and inflammatory markers. At six months the biggest contributor to response was patient global assessment. This shows that JAK inhibitors might mediate their response initially mostly through pain modulation then by inflammation as exposure to drug continues. References: [1]N Engl J Med. 2017 Feb 16;376(7):652-662 [2]N Engl J Med. 2014 Jun 19;370(25):2377-86 Disclosure of Interests: Clerin Joseph: None declared, Syed Mujtaba Bilgrami Speakers bureau: Pfizer, Lesley Ottewell: None declared, Leanne Gray: None declared, William Mitchell: None declared, Fiona Wood: None declared, Marco Massarotti: None declared, Marwan Bukhari Speakers bureau: Bristol-Myers Squib, UCB celltech, Roche/Chugai, Pfizer, Abbvie, Merck, Mennarini, Sanofi-aventis, Eli-Lilly, Janssen, Amgen and Novartis.